Pacific white shrimp (Litopenaeus vannamei) shell chitosan and the conjugate with epigallocatechin gallate: Antioxidative and antimicrobial activities. Issue 1 (29th November 2020) - Mittal, Ajay; Singh, Avtar; Aluko, Rotimi E.; Benjakul, Soottawat
Abstract: Chitin was isolated from Pacific white shrimp ( Litopenaeus vannamei ) shell by demineralization and deproteinization using 1 M HCl (1:20, w/v) for 2 hr and 1 M NaOH (1:30 w/v) for 80 min at 70ºC, respectively, with 29.96% optimum yield. Thereafter, the chitin was deacetylated at various temperatures for different times, in which the chitosan prepared at 130ºC for 4 hr (CS‐130‐4) showed higher yield (73.11%), crystallinity index (19.75%), and 85.28% degree of deacetylation (DDA) as measured by 1 H‐NMR. CS‐130‐4 was then conjugated to epigallocatechin gallate (EGCG) at various concentrations (2–8%, w/w of chitosan). CS‐130‐4 was grafted with 8% EGCG (CE‐8) had the higher conjugation efficiency (92.63%) and antimicrobial/antioxidant activities as compared to other conjugates ( p  < .05). 1 H‐NMR analysis also confirmed the successful conjugation of CE‐8. All the conjugates were completely water soluble. Therefore, CE‐8 may be used as the natural antimicrobial and antioxidant agents in various food products. Practical applications: Shrimp shells are generally considered as processing by‐products of the shellfish industries and can cause environmental pollution when improperly disposed. Chitosan from shrimp shells has been widely produced but it is soluble mainly in acidic solutions, which limits its applications. However, grafting of epigallocatechin gallate (EGCG) onto chitosan yielded water‐soluble conjugates with enhanced antioxidant and antimicrobial properties. Although several preservatives have been applied in foods, their health hazards have been a major concern. To mitigate this limitation, chitosan‐EGCG conjugates could be employed as alternative natural preservatives or additives for shelf‐life extension of various foods. Abstract : Chemical‐assisted extractions of chitin and chitosan from Pacific white shrimp shell were successfully optimized. Chitosan was effectively grafted with varying (2–8%, w/w) epigallocatechin gallate (EGCG) via the free radical grafting method. The conjugate from 8% ECGC conjugation (CE‐8) showed higher increases in antioxidant and antimicrobial activities among all other conjugates.